Sistem Monitoring Tracking Untuk Mengetahui Posisi Driver Kendaraan Menggunakan Geocoding Berbasis Android - Fatiby, Ubay; Jatmika, Sunu (Institut Tekonologi dan Binisi Asia Malang, 2024)
Masple tour and travel is a vehicle rental service in Mojokerto at affordable prices but still prioritizes service and quality. Based on the research conducted, there are problems in tracking and monitoring vehicles, driver delays in returning vehicles that have been rented, and also criminal acts such as travel vehicles that are run away by irresponsible drivers, so the explanation from Masple Tour and Travel when the author made study. This study uses geocoding to convert latitude and longitude coordinates into an address that will be displayed on Android based maps. One of the features contained in Android is internet service and is equipped with a GPS (Global Positioning System) feature, which is a navigation system that uses satellite signals in its use. With the GPS admin can find out the coordinates of the vehicle driver anywhere. This research resulted in a tracking monitoring system application to determine the position of vehicle drivers using Android-based geocoding. It is hoped that this tool will be able to minimize crimes such as vehicle theft by tracking the current position of the vehicle driver and displaying the latitude and longitude coordinates so that when a theft crime occurs, they can immediately take action.